The Clergy and Art Therapy - Kae-Jé, Bert (The Journal of pastoral care, 1998)
Defines the professional minister as subject to confining social attitudes and expectations. Posits clergy as good candidates for art therapy. Reports on a small pilot study that field tested a curriculum exploring the relationship between preaching and mental health and made use of several art activities. Uses results of this study to illustrate art therapy's potential to free clergy for authentic expression and to explore the potential and the problems posed by clergy as a target group for additional research.